About Medicolegal Evaluation of the Effects of Bone Fracture/Dislocation on Life Functions - Çelik, Cemil; Ata, Uğur (The Bulletin of Legal Medicine, 2022)
Article 87/3 of the Turkish Penal Code (TPC) indicates that if a deliberate injury causes bone fracture/dislocation in the body, it leads to penalty increase regarding its effects on the victim’s life functions. This study intends to discuss the concept of “the effects of bone fracture/dislocation on a person’s life functions”, considering both the legal and medical dimensions, and it provides solutions to the potential problems by addressing this issue regarding the Supreme Court’s decisions. The effects of bone fracture/dislocation in the legal literature focus on to what extent the fracture influences the victim’s daily life, whether the victim maintains his/her everyday life, whether he/she is able to do his/her job. The effects are determined in reference to “The Guideline of Evaluating Bodily Injury Offences in the TPC from Forensics Perspective”. However, in the guide, the effects of bone fracture/dislocation on life functions reflects the severity of fracture / dislocation and trauma. Although the guideline facilitates the standardization in this issue, it has noticeable limitations in legal principle of equality. There emerges a need for scale to provide objective and scientific data about the effects of fracture/dislocation. This research presents several validated and reliable scales to be used in Forensics and offers a method of calculating more than one fracture.